2020
DOI: 10.1002/acr.24062
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Delays Associated With Prior Authorization for Infusible Medications: A Cohort Study

Abstract: Objective. Prior authorizations (PAs) are commonly used by insurers as cost-containment strategies for expensive medications, including infused biologics. There is scarce data about the effect of PA requirements on patient-oriented outcomes. Methods. We included patients for whom an infusible medication was prescribed for a rheumatologic condition. The exposures of interest were a PA requirement and whether or not the PA was denied. The primary outcome was the difference in days from medication request to infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…In the years following implementation of PA, just 1.5% of all claims for tonsillectomy were denied approval. Our findings are similar to those of other studies that demonstrate very low denial of PA claims (<4%) for elective surgery, prescription medications, and imaging studies 13,15–17 . Furthermore, no statistically significant reduction in the incidence of tonsillectomy was discovered after implementation of PA for government plans alone, commercial plans alone, or all plan types combined.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the years following implementation of PA, just 1.5% of all claims for tonsillectomy were denied approval. Our findings are similar to those of other studies that demonstrate very low denial of PA claims (<4%) for elective surgery, prescription medications, and imaging studies 13,15–17 . Furthermore, no statistically significant reduction in the incidence of tonsillectomy was discovered after implementation of PA for government plans alone, commercial plans alone, or all plan types combined.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies demonstrated weeks-long delays in medication and infusions approvals, which led to increased adverse events and exposures or abandonment of the therapy entirely. 14,17,26 Although outside the scope of this study, there are concerns that PA is time-consuming and may result in additional money spent to process claims. One study evaluation PA for prescription medications in pediatric hematology and oncology noted that 20% of claims that were initially denied PA (1) did not actually need PA and were therefore approved or (2) were approved after the filing of additional paperwork or with a change in prescription.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, PA-related cost restrictions create delays that result in patients abandoning prescriptions [17]. These findings have been replicated across a number of specialties including rheumatology, psychiatry, primary care, oncology, infectious disease, and dermatology [9,11,13,14,15,16].…”
Section: Introductionmentioning
confidence: 82%
“…There is also growing evidence that the medication PA process can delay patient care and contribute to adverse patient outcomes. This has been noted in rheumatologic care with infusible treatments initially denied [13] as well as other medical specialties [9,11,14,15,16]. When surveyed, 24% of physicians noted that PA had led to a serious adverse event in one of their patients, 91% reported that PA requirements cause care delays, and 90% reported that PA delays resulted in worse patient outcomes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Prior Authorizations (PAs): Advocacy for streamlining PAs [96] is essential to improve patient survival and outcomes. Further, denials lead to higher insurance company costs [97], as most clinicians finally attain authorization [98]. An organized approach can expedite most procedures and medication authorizations, including an appeal, within 72 h in the US.…”
Section: Implementing the Planmentioning
confidence: 99%